Prevalence of blaTEM, blaSHV, and blaCTX-M Genes among ESBL-Producing Klebsiella pneumoniae and Escherichia coli Isolated from Thalassemia Patients in Erbil, Iraq - Pishtiwan, Ahmad Hamad (Mediterr J Hematol Infect Dis, 2019)
BACKGROUND: Due to the recent appearance of organisms that are resistant to several drugs (multidrug-resistant) like Enterobacteriaceae that produce extended-spectrum β-lactamase (ESBL, concerns have remarkably increased regarding the suitable treatment of infections. The present study was an investigation into ESBL molecular characteristics among clinical isolates of Klebsiella pneumoniae and Escherichia coli resulting in urinary tract infections (UTIs) and their pattern of antimicrobial resistance in order to come up with helpful information on the epidemiology of these infections and risk factors accompanied with them. METHODS: In order to conduct the study, 20 K. pneumoniae and 48 E. coli were isolated and retrieved from thalassemia center in Erbil, Iraq during July 2016 and September 2016. The collected strains were analyzed and the profile of their antimicrobial susceptibility was specified. In order to spot β-lactamase genes (i.e. blaTEM, blaSHV, and blaCTX-M), polymerase chain reaction was conducted. RESULTS: The findings obtained from multiplex PCR assay showed that out of the collected strains of ESBL-producing E. coli, had 81% blaTEM, 16.2% blaSHV, and 32.4% blaCTX-M genes. Similarly, 64.7% blaTEM, 35.2% blaSHV, and 41.1% blaCTX-M genes existed in the isolates of K. pneumoniae. It was found that antibiotic resistance pattern of E. coli and K. pneumoniae isolates to 20 antibiotics varied widely. It was also concluded that the majority of the K. pneumoniae and E. coli isolates were multi-drug resistant (MDR). Moreover, 75% and 87.5% of respectively K. pneumoniae and E. coli isolates showed the MDR phenotypes. CONCLUSION: TEM prevalence was high among other types of ESBLs. Over all, the most active antimicrobial agents in vitro remained to be the carbapenems.